Open Data in Power Grid Modelling: New Approaches Towards Transparent Grid Models. (November 2017) - Medjroubi, Wided; Müller, Ulf Philipp; Scharf, Malte; Matke, Carsten; Kleinhans, David
Abstract: In order to analyse the mid- and long-term impacts of energy related policies, different modelling approaches can be derived. However, the results of even the best energy system model will highly depend on the underlying input data. First, in this contribution the importance and availability issues of grid data in the context of energy system modelling are highlighted. Second, this paper focuses on power grid modelling based on open and publicly available data from OpenStreetMap using open source software tools. Two recent approaches developed to build electrical transmission network models using openly available data sources are presented and discussed. The proposed methods provide transparent assumptions, simplifications and documentation of grid modelling. This results in the ability of scientists and other stakeholders to validate, discuss or reproduce the results of energy system models. Thus the new open approaches offer a unique opportunity to increase transparency, comparability and reproducibility of results in energy system modelling.